DIGITAL CITIZENSHIP EDUCATION IN THE 21ST CENTURY: CHALLENGES AND OPPORTUNITIES - Ahmadova Kamola Ahmad qizi; Qalandarova Shahnoza Olim qizi (Modern American Journals, 2025)
This article explores the significance of digital citizenship education in the 21st century. With the rapid expansion of digital technologies, it is essential to equip learners with the knowledge, skills, and ethical framework necessary to navigate digital environments responsibly. This paper examines key concepts, challenges, and best practices in digital citizenship education globally and offers recommendations for future educational policy and curriculum development.
Keywords: Digital Citizenship, Education, Technology, Ethics, Media Literacy, Digital Skills, Policy.